Analysis of Education for Socialization and Understanding of Accounting Science in Business Development of Micro, Small and Medium Enterprises in Medan City - Lailatun Nafisa; Ratnawita Ratnawita; Prety Diawati; Hermiyetti Hermiyetti; Abdurohim Abdurohim (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze of education for socialization and understanding of accounting science in business development of Micro, Small, and Medium Enterprises in Medan City. The object of research at Micro, Small, and Medium Enterprises in Medan City. Population in this study are 8,212 Entrepreneurs of Micro, Small, and Medium Enterprises in 2022 in Medan City. Using the slovin formula, the research sample are 100 Entrepreneurs of Micro, Small, and Medium Enterprises in Medan City. The method of data analysis in this study used multiple linear regression using partial test (t). The results of the study show that socialization has a significant effect on business development of Micro, Small, and Medium Enterprises in Medan City. Understanding of accounting science has a significant effect on business development of Micro, Small, and Medium Enterprises in Medan City.